Dynamics of hypernuclear nonmesonic weak decay - Krmpotić, Franjo; Deppman, Airton; De Conti, Claudio [UNESP] (My University, 2012)
Simple and coincidence spectra of the NM weak decay of light hypernuclei have been evaluated in a systematic way for the first time. We have only considered 1N induced processes, neglecting entirely the events induced by 2N emission, as well as the effects of the FSIt's. As the theoretical frameworkwe have used the IPSM with three different parametrizations for the transition potential. The comparison with data strongly suggests that the soft π + K exchange model could be a good starting point to describe the dynamics in the NM weak decays of s- and p-shell hypernuclei. © 2012 American Institute of Physics.
Keywords: nonmesonic weak decay; one-meson-exchange: independent-particle shell model